2021
DOI: 10.1371/journal.ppat.1009571
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal dynamics of SARS-CoV-2 lineages during the first epidemic wave in New York City

Abstract: During the first phase of the COVID-19 epidemic, New York City rapidly became the epicenter of the pandemic in the United States. While molecular phylogenetic analyses have previously highlighted multiple introductions and a period of cryptic community transmission within New York City, little is known about the circulation of SARS-CoV-2 within and among its boroughs. We here perform phylogeographic investigations to gain insights into the circulation of viral lineages during the first months of the New York C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…Some phylodynamic models allow for explicit modelling of sampling bias, and this has enhanced several SARS-CoV-2 studies 12 , 25 , 100 . In some cases, a single uniquely shared variant may be sufficient to determine the origin of a transmission chain 60 , 101 , and in studies in which one or several regions or periods were poorly sampled, unsampled individuals have been modelled and added to analyses 102 , or unobserved ancestral locations jointly inferred using phylogenies 103 . Delays between case detection 104 and genome sequence availability, as well as insufficiently dense sampling, can hinder outbreak analysis.…”
Section: Tackling Sampling Bias In Genomic Epidemiologymentioning
confidence: 99%
“…Some phylodynamic models allow for explicit modelling of sampling bias, and this has enhanced several SARS-CoV-2 studies 12 , 25 , 100 . In some cases, a single uniquely shared variant may be sufficient to determine the origin of a transmission chain 60 , 101 , and in studies in which one or several regions or periods were poorly sampled, unsampled individuals have been modelled and added to analyses 102 , or unobserved ancestral locations jointly inferred using phylogenies 103 . Delays between case detection 104 and genome sequence availability, as well as insufficiently dense sampling, can hinder outbreak analysis.…”
Section: Tackling Sampling Bias In Genomic Epidemiologymentioning
confidence: 99%
“…We modelled the phylogenetic diffusion and spread of these lineages within Brazil by analysing localized transmission (between Brazilian regions) using a flexible relaxed random walk (RRW) diffusion model 51,52 that accommodates branch-specific variation in rates of dispersal with a Cauchy distribution and a jitter window site of 0.01 52 . The choice of Cauchy distribution was based on recent studies demonstrating that it is successful for this kind of analyses based on genomes of SARS-CoV-2 and its variants 4,50,[54][55][56] . For each sequence, latitude and longitude coordinates were attributed.…”
Section: S7)mentioning
confidence: 99%
“…While the outbreak in Italy has been traced phylogenetically to the Lombardy region, it remains unclear how exactly it started out and spread ( 62 ). A more recent phylogenetic study of viral samples from New York state during March–May 2020 confirmed the importance of Queens as a major transmission hub and provided supporting evidence of widespread geographic dispersion ( 63 ). Only 22% of the samples from New York City, however, were collected before the last week of March ( 64 ).…”
Section: Discussionmentioning
confidence: 87%